Bacterial dysbiosis and decrease in SCFA correlate with intestinal inflammation following alcohol intoxication and burn injury - Xiaoling Li; Caroline J Herrnreiter; Mary Grace Murray; Marisa Luck; Chirag Ganesa; Paulius V Kuprys; Mashkoor A Choudhry (eGastroenterology)
Background Patients intoxicated at the time of burn experience increased rates of sepsis and death compared with that observed in similarly sized burns alone. We sought to characterise changes in the intestinal microbiome and short-chain fatty acids (SCFAs) following alcohol intoxication and burn injury and to determine whether these changes are associated with intestinal inflammation.Methods 10–12-week-old C57BL/6 male and female mice were subjected to ethanol intoxication and a 12.5% total body surface area scald burn injury. The following day, mice were euthanised and faecal contents from the caecum and small intestine (SI) were harvested for 16S sequencing for microbial analysis and caecum contents underwent high-performance liquid chromatography mass spectroscopy to assess SCFAs.Results The intestinal microbiome of ethanol burn (EB) mice exhibited decreased alpha diversity and distinct beta diversity compared with sham vehicle (SV). EB faeces were marked by increased Proteobacteria and many pathobionts. EB caecum faeces exhibited a significant decrease in butyrate and a downward trend in acetate and total SCFAs. SCFA changes correlated with microbial changes particularly in the SI. Treatment of murine duodenal cell clone-K (MODE-K) cells with faecal slurries led to upregulation of interleukin-6 (IL-6) from EB faeces compared with SV faeces which correlated with levels of Enterobacteriaceae. However, supplementation of butyrate reduced faecal slurry-induced MODE-K cells IL-6 release.Conclusion Together, these findings suggest that alcohol and burn injury induce bacterial dysbiosis and a decrease in SCFAs, which together can promote intestinal inflammation and barrier disruption, predisposing to postinjury pathology.